Оцінка діючого механізму залучення фінансових ресурсів в аграрний сектор економіки на умовах фінансового лізингу - Яцух, Олена Олексіївна; Яцух, Елена Алексеевна; Yatsuh, Olena (Мелітополь: ТДАТУ, 2017)
UK: В даній статті обґрунтовано науково-практична значимість розвитку лізингових відносин, як одного із дієвих фінансових методів розширеного відтворення основних засобів в аграрному секторі економіки. Дана оцінка діючому механізму формування лізингових платежів та основних складових, які впливають на їх розмір. Проведено аналіз динаміки та структури обсягів ресурсів залучених на існуючому ринку лізингових послуг в Україні та світі. EN: The scientific and practical significance of the development of leasing relations as one of the effective financial methods of expanded reproduction of fixed assets in the agrarian sector of the economy are substantiated in this article. The growth rates of agricultural production in the Ukrainian economy grow by volume, and according to official statistics, the profitability of production in the industry increases; however, the level of suitability of the main means of production is reduced and remains critical at the level of more than 40%. The probable cause of such contradictions may be the fact that the industry remains low-tech with the use of outdated production technologies, especially as regards the processing, storage and manufacture of finished products. The market for such services remains imperfect. Leasing operations, in such conditions, may be one of the main sources of financing for the restoration of the material and technological base for the production of high-end, high-end finished agricultural products. The analysis of dynamics and structure of the volume of resources attracted on the existing market of leasing services in Ukraine and in the world are carried out. According to the generalized information, the value of financial leasing contracts increased in Ukraine with UAH 4.9 billion in 2006 to 67.1 billion UAH in 2013, and it has fallen critically in the period of the financial crisis to 26.3 billion UAH in 2015. The share of contracts with the lenders representing the agrarian sector in Ukraine varies considerably over the analyzed period, in 2006 it was equal to 18%, in 2008 it was only 8%, in 2015 it increased to 25.2%. The total value of financial leasing contracts for the purchase of machinery, machinery, equipment for agricultural enterprises of Ukraine reached UAH 8,846.8 million in 2014. As a result, the estimation of operating mechanism for formation of lease payments and the main components that affect their size are given. Determining the size of leasing payments is essential for the development of the leasing market. The total amount of lease payments for the entire period of the lease includes: the amount that compensates for the costs of production or acquisition of leased property; overhead costs, as well as operating costs; the cost of credit resources used to purchase property under a lease agreement, while it is necessary in the conditions of the financial crisis to foresee losses from the impairment of property as a result of inflation; marketing expenses and aggregate leasing company's services; obligatory expenses for property insurance; profit (margin) of the lessor;
Evaluation of the effective mechanism of financing resources in the agricultural sector of the economy on financial leasing conditions
Keywords: джерело фінансування; ринок фінансових послуг; лізинг; лізингова угода; лізинговий платіж; лізингова компанія; лізингодавець; лізингоодержувач; source of financing; financial services market; leasing; leasing agreement; lease payment; leasing company; lessor; lessee